2012
DOI: 10.1007/s00115-011-3418-0
|View full text |Cite
|
Sign up to set email alerts
|

„Quality of reporting“ in Studien zur bipolaren Störung

Abstract: Clinical investigators as well as editors and reviewers should be further encouraged to follow publication guidelines otherwise trials have to be downgraded or excluded from systematic evaluations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…A recent review of 134 RCTs on pharmacological treatment of bipolar disorder published between 2000 and 2010 found that while some trial-related information is well reported a good part of the reporting quality of RCTs in bipolar disorder falls well below the required level as aimed for by CONSORT [17], [18]. Twenty-five percent (n = 18) of all CONSORT items were generally reported inadequately (reported adequately in less than 25% of all trials).…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of 134 RCTs on pharmacological treatment of bipolar disorder published between 2000 and 2010 found that while some trial-related information is well reported a good part of the reporting quality of RCTs in bipolar disorder falls well below the required level as aimed for by CONSORT [17], [18]. Twenty-five percent (n = 18) of all CONSORT items were generally reported inadequately (reported adequately in less than 25% of all trials).…”
Section: Introductionmentioning
confidence: 99%